How Currents Trigger Extreme Sea Waves. The Roles of Stokes Drift, Eulerian Return Flow, and a Background Flow in the Open Ocean - Yan Li; Amin Chabchoub (Geophysical Research Letters)
Abstract A deterministic system of ocean surface waves and flow in the oceanic boundary layer is key to understanding the dynamics of the upper ocean. For the description of such complex systems, a higher‐order shear‐current modified nonlinear Schrödinger equation is newly derived and then used to physically interpret the interplay between Stokes drift, Eulerian return flow due to a passing wave group, and an open‐ocean vertically sheared flow in the extreme sea wave generation. The conditions for the suppression or enhancement of the modulation instability in the rogue wave dynamics in the presence of a background flow are reported, whose relevance and influence to the Craik‐Leibovich type 2 instability in triggering a Langmuir‐type circulation is discussed. The findings highlight the need for future studies to establish and assess the energy transfer from waves to currents or in the reversing order, asserting a plausible physical mechanism for the dissipation of the surface wave energy through wave‐current interactions in the open ocean.